Le « marché aux putains » : économies sexuelles et dynamiques spatiales du Palais-Royal dans le Paris révolutionnaire - Clyde Plumauzille (Genre, Sexualité et Société)
The Palais-Royal enjoys a special place in the urban mythology of the Paris Galant, capital of pleasure and debauchery for European elites in the eighteenth-century. This sexual and economic enclave, a space exemplary of a new geography of sexual entertainment in major European cities, provides a window into the redefinition of the relationship between trade and sexuality at the turn of the century. In the Revolutionary period, the decline of the great Ancien Regime brothels, the increase of the number of Parisian prostitutes, and the decriminalization of prostitution in 1791 through the new Criminal and Correctional Codes, put the Palais-Royal on the front of the prostitutional scene: the latter, according to the observer Louis-Sébastien Mercier, then concentrated in a “dot” the whole prostitution scandal of the capital. This article will question the in situ exceptional nature of this space devoted to prostitution at the end of the century and the first sex market in the capital.